Pandemic and the Critical Role of Knowledge Management - Gulsecen, Sevinc; Sharma, Sushil Kumar; Kocoglu, Fatma Onay (Istanbul University Press, 2023)
COVID-19 has been one of the worst pandemics of the century due to its high contagiousness emerging like a Black Swan phenomenon, which created crises worldwide in the health systems, economies, financial systems, retail markets, tourism, and hospitality industries, educational systems, and employment. It created an unprecedented disruption and lockdowns in all the domains of our life. The world was caught unprepared for disruptive power to handle the crises. Before the COVID-19, emergent contagious diseases such as avian influenza, MERS, SARS, and Ebola had produced many deaths and showed the power of an epidemic in many countries worldwide. However, the novel coronavirus pneumonia (COVID-19) was more challenging and devastating. Due to the extended lockdowns and virtual work situations, the COVID-19 pandemics necessitated the organizations to exploit knowledge and creativity for their survival and growth. To handle the lifetime crises, organizations started using knowledge management as a strategic resource to mitigate health and socio-economic effects. Effective knowledge management (KM) practices helped organizations launch effective countermeasures against such crises. This book on "Pandemic and the Critical Role of Knowledge Management" comprises twenty (20) chapters covering the critical role of knowledge management during COVID-19 pandemics.